(untitled) (The Journal of Psychology and Sociology, 2017)
This article is dedicated to one of the most important problems to help children with Down syndrome. The object of this study is especially the mental development of a child with Down syndrome. Subject of research - correctional and development work aimed at the development and education of a child with Down syndrome. In this article, the authors considered Kazakhstan and foreign works dedicated to the education and training of children with Down syndrome. Investigate the features of various aspects of mental activity of the child with Down syndrome, propose corrective parenting programs, training and development of a child with Down syndrome. The main idea of correctional work with children with Down syndrome are their social adaptation, adaptation to life and integration into society, using all the cognitive abilities of children, and, given the specificity of the development of mental processes, to develop their life skills that, becoming adults, they can independently take care of themselves, perform simple work at home, to improve the quality of their lives and the lives of their parents. Having studied the international experience of work on this issue, author says of the need to develop the skills of cultural behavior in dealing with people, teach them communication skills. They should be able to express request, be able to defend themselves or avoid the danger. Much attention should be paid to the external forms of behavior. According to the scientists at all stages of life of children with Down syndrome should be under the auspices of the experts, the process of organizing these people to support the educational and social space. It is this approach, according to scientists, can achieve the best results in this category of children and contributes to the realization of the maximum of their available potential. Just as the results of foreign and domestic specialists, due to these correctional programs it is possible to not only bring a new level of development of the child itself, but also largely determines the progress of social adaptation and integration of the child with special needs into society. Key words: Down syndrome, chromosome, social work, integration.